A multi-agent based security policy for web related applications: a hybrid approach using context and ontology. (2017) - Cheribi, Haoua; Bouramoul, Abdelkrim; Kholladi, Mohamed Khireddine
In this paper, we present a multi-agent system model based, for securing computer systems that operate in complex and pervasive environments, such as web applications. These applications are characterised by unpredictable changes in terms of resources and circumstances. The choice of the multi-agent systems paradigm is motivated by its suitability to this type of problems, in terms of autonomy, flexibility and scalability. Therefore, we propose a hybrid approach considering the execution context to express the circumstances and conditions of the environment. The purpose is to better interact with users and respond effectively to the posed situation. Furthermore, the use of ontologies that enrich the considered system by semantics, strengthen the proposed approach by increasing the objectivity and overcome any ambiguities caused by the heterogeneity of the different intervening entities. So, the proposed model aims to respond to some security problems for information systems related to web, as well as to improve it in terms of relevance, clarity and objectivity.